Corruption as a Factor of Political Instability: The Path to Sustainable Development Through Civil Society - Alievich, Abduganiev Jamshid (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
Corruption remains a pervasive issue with significant societal impacts, yet its underlying causes and effective solutions are not fully understood. This study explores the root causes of corruption, drawing on a comparative analysis of international experiences to identify common patterns and challenges. Addressing a knowledge gap in understanding the interplay between corruption and societal development, the research employs a multidisciplinary approach, including qualitative analysis of corruption-related issues. The findings highlight critical factors driving corruption and propose actionable recommendations to mitigate its effects. The study provides insights for policymakers and stakeholders, emphasizing the importance of targeted strategies to reduce corruption and promote societal integrity.